Laterality Influences Central Integration of Baroreceptor Afferent Input in Male and Female Sprague Dawley Rats - Salman, Ibrahim M.; Ameer, Omar Z.; McMurray, Sheridan; Giarola, Alessandra S.; Sridhar, Arun; Lewis, Stephen J.; Hsieh, Yee-Hsee (Frontiers in Physiology, 2020)
We explored the effects of baroreceptor afferents laterality and sexual dimorphism on the expression of cardiovascular reflex responses to baroreflex activation in Sprague Dawley (SD) rats. Under urethane anesthesia, rats of either sex (total n=18) were instrumented for left, right and bilateral aortic depressor nerve (ADN) stimulation (1–40 Hz, 0.2 ms, 0.4 mA for 20s) and measurement of mean arterial pressure (MAP), heart rate (HR) and mesenteric (MVR) and femoral (FVR) vascular resistance. Female rats were matched for the diestrus phase of the estrus cycle. Left, right and bilateral ADN stimulation evoked frequency-dependent drops in MAP, HR and MVR, and increases in FVR. Irrespective of sex, left and bilateral ADN stimulation as compared to right-sided stimulation mediated greater reflex reductions in MAP, HR and MVR but not in FVR. In males, reflex bradycardic responses were greater in response to bilateral stimulation relative to both left- and right-sided stimulation. In females, left ADN stimulation evoked the largest increase in FVR. Left and bilateral ADN stimulations evoked greater reductions in MAP and MVR while left-sided stimulation produced larger increases in FVR in females compared with males. All other reflex responses to ADN stimulation were relatively comparable between males and females. These results show a differential baroreflex processing of afferent neurotransmission promoted by left versus right baroreceptor afferent inputs and sexual dimorphism in the expression of baroreflex responses in rats of either sex. Collectively, these data add to our understanding of physiological mechanisms pertaining to baroreflex control in both males and females.